Role of students' context in predicting academic performance at a medical school: a retrospective cohort study. Issue 3 (11th March 2016) - Thiele, Tamara; Pope, Daniel; Singleton, A; Stanistreet, D
Abstract : Objectives: This study examines associations between medical students' background characteristics (postcode-based measures of disadvantage, high school attended, sociodemographic characteristics), and academic achievement at a Russell Group University. Design: Retrospective cohort analysis. Setting: Applicants accepted at the University of Liverpool medical school between 2004 and 2006, finalising their studies between 2010 and 2011. Participants: 571 students (with an English home postcode) registered on the full-time Medicine and Surgery programme, who successfully completed their medical degree. Main outcome measures: Final average at year 4 of the medical programme (represented as a percentage). Results: Entry grades were positively associated with final attainment (p<0.001). Students from high-performing schools entered university with higher qualifications than students from low-performing schools (p<0.001), though these differences did not persist at university. Comprehensive school students entered university with higher grades than independent school students (p<0.01), and attained higher averages at university, though differences were not significant after controlling for multiple effects. Associations between school type and achievement differed between sexes. Females attained higher averages than males at university. Significant academic differences were observed between ethnic groups at entry level and university. Neither of the postcode-based measures of disadvantage predicted significant differences in attainment at school or university. Conclusions: The findings of this study suggest that educational attainment at school is a good, albeit imperfect, predictor of academic attainment at medical school. Most attainment differences observed between students either decreased or disappeared during university. Unlike previous studies, independent school students did not enter university with the highest grades, but achieved the lowest attainment at university. Such variations depict how patterns may differ between subjects and higher-education institutions. Findings advocate for further evidence to help guide the implementation of changes in admissions processes and widen participation at medical schools fairly.